Circulating prolactin levels and Behcet’s disease: A meta-analysis - Song, Gwan Gyu; Lee, Young Ho (Cellular and Molecular Biology, 2018)
This study aimed to summarize the current evidence on the relationship between circulating prolactin levels and Behcet’s disease (BD). We performed a meta-analysis comparing the serum/plasma prolactin levels in patients with BD with those of controls and performed a subgroup analysis based on ethnicity, disease activity, and sex. Ten articles with a total of 320 patients with BD and 259 controls were included. The prolactin levels were not significantly higher in the BD group than in the control group (SMD=0.208, 95% CI=-0.012–0.428, p=0.064). Stratification by ethnicity indicated no elevation in prolactin level in Turkish patients with BD (SMD=0.127, 95% CI=-0.111–0.366, p=0.295). Stratification by disease activity revealed no elevation in prolactin level in both the active and inactive BD groups compared with the control group (SMD=0.373, 95% CI=-0.095–0.841, p=0.119; SMD=0.055, 95% CI=-0.243–0.354, p=0.717). Stratification by sex revealed no elevation in prolactin level in both the female and male BD groups (SMD=0.031, 95% CI=-0.398–0.460, p=0.888; SMD=0.279, 95% CI=-1.411–1.969, p=0.746). The prolactin levels were not significantly elevated in patients with BD, regardless of the adjustments for age/sex, sample size, or data type evaluated. This meta-analysis of current evidence suggests that circulating prolactin levels may not be higher in patients with BD than in controls.